2017
DOI: 10.1145/3154491
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Mean Field Approximation

Abstract: Mean eld models are a popular means to approximate large and complex stochastic models that can be represented as N interacting objects. Recently it was shown that under very general conditions the steady-state expectation of any performance functional converges at rate O(1/N ) to its mean eld approximation. In this paper we establish a result that expresses the constant associated with this 1/N term. This constant can be computed easily as it is expressed in terms of the Jacobian and Hessian of the drift in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…but on the other hand we must have G i (t) = G i (x(t)), where G i is defined in (10). We have thus shown thaṫ…”
Section: Lemma 12mentioning
confidence: 77%
See 1 more Smart Citation
“…but on the other hand we must have G i (t) = G i (x(t)), where G i is defined in (10). We have thus shown thaṫ…”
Section: Lemma 12mentioning
confidence: 77%
“…• Server selections can be made without replacement, instead of with replacement. In view of the results in Gast and Van Houdt [10], this may also improve the convergence speed of X N to fluid solutions.…”
Section: Global Stabilitymentioning
confidence: 96%
“…In Ying (2019, 2020), Liu et al (2022), the authors used Stein's method for mean-field analysis to obtain bounds on steady-state performance metrics of interest, like EQ 2 for instance, for the power-of-d system. Another line of work on power-of-d systems was by Gast (2017), Gast and Van Houdt (2017), Gast et al (2019), where the authors showed how to derive refined mean-field models for improved steady-state approximations. More recently, Hairi et al (2021) provide calculable error bounds for the mean-field approximation of the power-of-two-choices model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key question is how well the mean-field limit describes the occupancy distribution and the blocking probabilities when N is finite but large. Recently, there have been a number of papers [6, 23] that have addressed this issue for M/M/1 queueing models for the case where the limiting stationary distribution can be characterized explicitly as a double-exponential distribution. They used an approach based on Stein’s method and showed that the rate of convergence of the empirical occupancy distribution to the mean-field distribution is .…”
Section: Introductionmentioning
confidence: 99%
“…They used an approach based on Stein’s method and showed that the rate of convergence of the empirical occupancy distribution to the mean-field distribution is . In [6] a refined term is also given. These approaches use Stein’s method and exponential stability of the underlying mean-field equation to study the mean-squared error between the empirical distribution and the mean-field limit to characterize the rate of convergence.…”
Section: Introductionmentioning
confidence: 99%